Ceramic Toughening Strategies for Biomedical Applications - Bai, Rushui; Sun, Qiannan; He, Ying; Peng, Liying; Zhang, Yunfan; Zhang, Lingyun; Lu, Wenhsuan; Deng, Jingjing; Zhuang, Zimeng; Yu, Tingting; Wei, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
Aiming at shortage of metal materials, ceramic is increasingly applied in biomedicine due to its high strength, pleasing esthetics and good biocompatibility, especially for dental restorations and implants, artificial joints, as well as synthetic bone substitutes. However, the inherent brittleness of ceramic could lead to serious complications, such as fracture and disfunction of biomedical devices, which impedes their clinical applications. Herein, several toughening strategies have been summarized in this review, including reinforcing phase addition, surface modification, and manufacturing processes improvement. Doping metal and/or non-metal reinforcing fillers modifies toughness of bulk ceramic, while surface modifications, mainly coating, chemical and thermal methods, regulate toughness on the surface layer. During fabrication, optimization should be practiced in powder preparation, green forming and densification processes. Various toughening strategies utilize mechanisms involving fine-grained, stress-induced phase transformation, and microcrack toughening, as well as crack deflection, bifurcation, bridging and pull-out. This review hopes to shed light on systematic combination of different toughening strategies and mechanisms to drive progress in biomedical devices.